2018
DOI: 10.1016/j.ijscr.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidural angiolipoma: A rare cause of spinal cord compression

Abstract: HighlightsSpinal epidural angiolipoma is a rare cause of progressive spinal cord compression.Magnetic resonance imaging is necessary for diagnosis.Total resection is the treatment of choice.Necessary precautions before and during surgery have to be taken (embolisation, transfusion).Prognosis after surgical management is excellent even at the stage of complete paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 10 Fast progression (acute) neurological symptoms might occur in some of the cases of these tumors and is attributed to vascular factors such as venous stasis with thrombosis, intratumoral bleeding, or steal phenomenon leading to an acute cord compression. 6 , 11–14 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Fast progression (acute) neurological symptoms might occur in some of the cases of these tumors and is attributed to vascular factors such as venous stasis with thrombosis, intratumoral bleeding, or steal phenomenon leading to an acute cord compression. 6 , 11–14 …”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is rare, with only one case reported in literature over 12 years of surgical resection [6]. While angiolipoma is relatively benign, without tissue diagnosis this could have been a different type of tumor and clinical outcomes could have differed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 SALs usually involve two to three vertebral segments, and lesions including more than six segments are rare. 8,13 The main features of SALs based on reported studies are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%